2022
DOI: 10.2196/31451
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Drivers Regarding the Use of Mobile Health Apps Among Patients With Type 2 Diabetes Mellitus in the Netherlands: Explanatory Sequential Design Study

Abstract: Background Self-monitoring of blood glucose levels, food intake, and physical activity supports self-management of patients with type 2 diabetes mellitus (T2DM). There has been an increase in the development and availability of mobile health apps for T2DM. Objective The aim of this study is to explore the actual use of mobile health apps for diabetes among patients with T2DM and the main barriers and drivers among app users and nonusers. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…App functions can facilitate supportive interaction by sharing data or app reports with clinicians and "loved ones" to gain support for behavior change. This is consistent with several studies that showed data sharing or showing data from the mobile devices with their clinicians during a medical visit is highly valuable for patients [50,54,55]. Greater app interactivity with a clinician appears to improve glycemic control [11,56].…”
Section: Connectivitysupporting
confidence: 89%
See 1 more Smart Citation
“…App functions can facilitate supportive interaction by sharing data or app reports with clinicians and "loved ones" to gain support for behavior change. This is consistent with several studies that showed data sharing or showing data from the mobile devices with their clinicians during a medical visit is highly valuable for patients [50,54,55]. Greater app interactivity with a clinician appears to improve glycemic control [11,56].…”
Section: Connectivitysupporting
confidence: 89%
“…Greater app interactivity with a clinician appears to improve glycemic control [11,56]. A simple explanation for this finding may be that successful diabetes self-management takes teamwork [54,55]. Informal coaching support by other people or even a virtual coach in an app is valuable.…”
Section: Connectivitymentioning
confidence: 99%
“…Although there is a wide array of apps currently available, they are not yet integrated in routine diabetes care. Previous studies have described that end users, staffing, technology, systems, clinical and cultural issues, and costs hinder the acceptance and implementation of mobile health apps for diabetes control and self-management in routine care [15][16][17][18].…”
Section: Apps For Diabetes Control and Self-managementmentioning
confidence: 99%
“…Most previous research in this area has focused on either the patient or DSN perspective; thus, studies that integrate aspects from both sides are lacking [14,15]. Notably, only 19 of 47 countries in Europe recognize diabetes nursing as a specialty and provide diabetes-specific education for nurses [16].…”
Section: Introductionmentioning
confidence: 99%